Telehealth in Oncology: ASCO Standards and Practice Recommendations. Issue 9 (September 2021) - Zon, Robin T.; Kennedy, Erin B.; Adelson, Kerin; Blau, Sibel; Dickson, Natalie; Gill, David; Laferriere, Nicole; Lopez, Ana Maria; Mulvey, Therese M.; Patt, Debra; Pickard, Todd A.; Purdom, Terry; et al.
Abstract : PURPOSE: To provide standards and practice recommendations specific to telehealth in oncology. METHODS: A systematic review of the literature on telehealth in oncology was performed, including the use of technologies and telecommunications systems, and other electronic methods of care delivery and sharing of information with patients. The evidence base was combined with the opinion of the ASCO Telehealth Expert Panel to develop telehealth standards and guidance. Public comments were solicited and considered in preparation of the final manuscript. RESULTS: The Expert Panel determined that general guidance on implementing telehealth across general and specialty settings has been published previously and these resources are endorsed. A systematic search for studies on topics specific to oncology resulted in the inclusion of two clinical practice guidelines, 12 systematic reviews, and six primary studies. STANDARDS AND GUIDANCE: Standards and guidance are provided for which patients in oncology can be seen via telehealth, establishment of the doctor-physician relationship, role of allied health professionals, role of advanced practice providers, multidisciplinary cancer conferences, and teletrials in oncology. Additional information is available at www.asco.org/standards .